Degradation, water uptake, injectability and mechanical strength of injectable bone substitutes composed of silk fibroin and hydroxyapatite nanorods (2018)
Injectable bone substitutes are generally composite materials capable of being extruded through a device; they consist of a solid phase inside a matrix that allows the easy movement of particles. Injectable bone substitutes have the advantage of allowing its application in situ without the need of invasive surgical techniques, guaranteeing a good recovery; for this reason, they are a promising alternative to replace conventional techniques to repair bone defects. Conventional techniques include the use of allografts and autografts, which often cause adverse reactions, and are disadvantageous for both the patient and the doctor. Furthermore, there are no reports regarding bone substitute development in Colombia, creating the necessity to research composite materials that could become injectable bone substitutes. In this study, we manufactured injectable bone substitutes with hydroxyapatite and calcium phosphate, which is most similar to bone tissue, and synthesized them in nanorods with shape and size similar to the natural hydroxyapatite found inside the body. Additionally, we used extracted silk fibroin from silkworm cocoons of Bombyx mori, a natural polymer of protein nature with high mechanical properties and excellent biocompatibility. For the materials manufactured, we evaluated degradation, in a simulated body fluid (SBF) at normal body temperature, water uptake, injectability and mechanical strength. The manufactured bone substitutes showed good degradation and water uptake properties, an approximate 97% injectability, and low mechanical resistance, indicating promising properties to be used as an injectable bone substitute.